2014
DOI: 10.1007/978-3-319-07995-0_8
|View full text |Cite
|
Sign up to set email alerts
|

Inventory Routing Problem with Stochastic Demand and Lead Time: State of the Art

Abstract: Abstract. The integration of the different processes that conform the supply chain (SC) is fundamental to obtain a better coordination level. The inventory control and its distribution, are the processes that researches have found as the key in the loss of efficiency and effectiveness in the field of logistics, affecting so the synchronization in the SC management. In order to analyze the recent developments in the integration of these processes, this paper analyzes the state of the art of the progress in info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Similarly, Refs. [18][19][20][21][22][23][24] are reviews of IRP models and classification of solutions; Refs. [21,22] both proposed the concept of sustainable logistics management.…”
Section: Previous Review Papersmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Refs. [18][19][20][21][22][23][24] are reviews of IRP models and classification of solutions; Refs. [21,22] both proposed the concept of sustainable logistics management.…”
Section: Previous Review Papersmentioning
confidence: 99%
“…Categorized IRPs with respect to their structural variants and with respect to availability. 1987-2012 130 [18] Proposed information management of IRP. Provided the relationship between inventory policy and demand information.…”
Section: Previous Review Papersmentioning
confidence: 99%
“…The variant of IPR, which consider both stochastic demand and time windows, is still hardly found, although almost similar study with lead time has been proposed by Roldan [32]. In this study, we extend the vehicle routing problem with stochastic demand and multi-item (VRPSDMI) problem proposed by Huang & Lin [6] and add the time window constraint for each retailer into the inventory routing problem with stochastic demand and time windows (IRPSDTW).…”
Section: Introductionmentioning
confidence: 96%
“…An overview of state of the art of IRPs is provided in Roldán, Basagoiti, and Onieva (2014) where some key elements were identified that should be taken into account to propose alternative solutions to DSIRPs. The information management between different stakeholders in the supply chain is one of them, since this determines the evolution and quality of shared information.…”
Section: Introductionmentioning
confidence: 99%